III Italian Consensus Conference on Malignant Mesothelioma of the Pleura. Epidemiology, Public Health and Occupational Medicine related issues - final document - Magnani, et al., Corrado (La Medicina del Lavoro, 2015)
di Corrado Magnani, Claudio Bianchi, Elisabetta Chellini, Dario Consonni, Bice Fubini, Valerio Gennaro, Alessandro Marinaccio, Massimo Menegozzo, Dario Mirabelli, Enzo Merler, Franco Merletti, Marina Musti, Enrico Oddone, Antonio Romanelli, Benedetto Terracini, Amerigo Zona, Carlo Zocchetti, Mariano Alessi, Antonio Baldassarre, Irma Dianzani, Milena Maule, Carolina Mensi, Stefano Silvestri Introduction The third Italian Consensus Conference on Pleural Mesothelioma convened in Bari on January 29th – 30th. Besides the main consensus report summarizing the contribution of the different expertises, that was published elsewhere (Pinto et al), the participants in the ‘Epidemiology, Public Health and Occupational Medicine’ section decided to report in major details the evidence and the conclusions regarding epidemiology, causative mechanisms and the public health impact of the disease. The working group on Epidemiology, Public Health and Occupational Medicine focused its activity on several issues selected because of new evidence emerged after the II Consensus Conference. The Group members proposed a selection of topics and the final program was agreed on during the first preparatory meeting (Dec 12th, 2014). The group agreed also on the inclusion of a summary on peritoneal MM. [...]